Preparation method of multi-layer alternating type super-hydrophobic self-cleaning water-based environment-friendly coating

Through the multi-layer alternating superhydrophobic self-cleaning water-based environmentally friendly coating method, the problem of degradation of hydrophobic performance of superhydrophobic coating in oil film environment is solved, and the hydrophobic performance of superhydrophobic coating is achieved. The long-lasting hydrophobic, anti-fouling and self-repairing effects of the coating improves the mechanical properties and service life of the coating.

CN119307155APending Publication Date: 2025-01-14SHENYANG INSTITUTE OF CHEMICAL TECHNOLOGY

Patent Information

Application Number
CN202411617705.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-14

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a water-based environment-friendly coating, in particular to a preparation method of a multi-layer alternating type super-hydrophobic self-cleaning water-based environment-friendly coating, which is characterized in that TiO2 / ZIF-8 micro-nano structure particles with photocatalytic performance are prepared by growing ZIF-8 on the surface of carboxylated modified TiO2 in situ. Perfluorodecyl trimethoxy silane (PFDTES) is used as a main substance with a hydrophobic function, and water-borne epoxy resin (EP) is introduced to hybridize water-borne fluorocarbon resin (FEVE) to serve as a bonding layer. The preparation method comprises the following steps: chemically bonding TiO2 / ZIF-8 / PFDTES and hybrid resin by gamma-aminopropyltriethoxysilane (KH550) carrying activation sites through a site regulation and control technology, so as to form the synergistically functionalized super-hydrophobic self-cleaning water-based environment-friendly emulsion. And the coating isolates the adhesion effect of most bacteria and the harm of domestic sewage. The photocatalytic function can degrade an oil film formed by pollutants such as organic substances and oil stains on the surface of the material. The multi-layer alternate functional coating greatly enhances the corrosion resistance of the substrate material, and prolongs the service life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a water-based environmentally friendly coating, and in particular to a method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating. Background Art

[0002] Waterborne paint is a type of paint that uses water as a solvent or dispersion medium. Compared with traditional solvent-based paints, it has significant environmental advantages. Its main feature is low volatile organic compound (VOC) emissions, which reduces pollution hazards to the environment and human health. With the improvement of global environmental awareness, waterborne paint has gradually become a popular choice in the paint industry. Today, waterborne paint is widely used in home decoration, automobiles, industry and other fields, representing a green and sustainable development direction of paint solutions.

[0003] Superhydrophobic coatings are widely used in many fields due to their remarkable water-repellent and antifouling capabilities. These coatings are usually effective in making water droplets form an almost perfect sphere when they contact the surface and roll off quickly, thus keeping the surface dry and clean. However, despite the excellent initial performance of superhydrophobic coatings, they often face the challenge of gradually declining performance in practical applications. This is mainly due to factors such as long-term wear, environmental factors, chemical corrosion, and mechanical scratches during daily use.

[0004] Although the existing inventions of super hydrophobic coatings all have excellent hydrophobic properties, their performance may be significantly reduced in long-term use or under specific environmental conditions. In particular, when the coating surface is exposed to an environment containing oil or other organic matter for a long time, these organic substances will gradually form a thin "oil film" on the surface. This oil film will significantly change the surface properties of the coating, resulting in a decrease in its hydrophobic performance. The presence of the oil film reduces the surface roughness and the contact angle, making it easier for water molecules to diffuse and stay on the coating surface.

[0005] To solve such problems, improving the oil resistance of coatings and enhancing their long-term stability have become the focus of research and industry. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating, which uses photocatalytic super-hydrophobic synergistically functionalized TiO2 / ZIF-8 / PFDTES particles as the structural site of the cross-linked network structure, and uses γ-aminopropyltriethoxysilane as the cross-linked network, and forms a synergistically functionalized super-hydrophobic self-cleaning water-based environmentally friendly emulsion through chemical bonding with water-based epoxy resin (EP) hybrid water-based fluorocarbon resin (FEVE). Using the deposited epoxy group as the connection between the super-hydrophobic water sand and the network structure, the three effects are cross-linked to prepare a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating. The multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating layer prepared by the present invention has excellent mechanical properties, strong anti-fouling ability, and lasting hydrophobic effect.

[0007] The present invention adopts the following technical solutions.

[0008] A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating comprises the following raw materials by weight: 10-15 parts of composite functional titanium dioxide, 50-100 parts of super-hydrophobic color sand, 3-5 parts of γ-aminopropyl triethoxysilane, 5-10 parts of water-based epoxy dispersion, 3-5 parts of water-based fluorocarbon resin, and 3-5 parts of water-based epoxy curing agent, specifically comprising the following steps: 13 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 4 parts of γ-aminopropyl triethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain a titanium dioxide gel solution A with activation sites. 5 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to gel B, and 50 parts of super-hydrophobic water sand were added, and the system was stirred at 300-500 r / min to make the system uniform to obtain a new water-based environmentally friendly emulsion. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained.

[0009] Furthermore, the steps for preparing composite functional titanium dioxide are as follows: 3 parts of succinic anhydride and 5 parts of γ-aminopropyltriethoxysilane are added to a beaker containing 50 parts of N,N-dimethylformamide, 1 part of 4-dimethylaminopyridine catalyst is added at 80°C, titanium dioxide is added after stirring at 500 r / min for 3 hours, stirring is continued for 2 hours, and centrifugal drying is performed to obtain carboxylated titanium dioxide. The carboxylated titanium dioxide is dispersed in 5 parts of anhydrous ethanol, 10 parts of zinc nitrate are added after ultrasonic dispersion for 10 minutes, and magnetic stirring is performed for 30 minutes before further use. After 10 parts of 2-methylimidazole are dispersed in 3 parts of anhydrous ethanol, they are added to the above solution, stirred continuously for 4 hours, and centrifuged to obtain TiO2 / ZIF-8. After 2 parts of TiO2 / ZIF-8 are dispersed in 10 parts of anhydrous ethanol, 1 part of perfluorodecyltrimethoxysilane is added, magnetic stirring is performed for 2 hours, and centrifugal drying is performed to obtain composite functional titanium dioxide.

[0010] Further, the preparation step of super-hydrophobic colored sand is as follows: 20 parts of anhydrous ethanol, 10 parts of distilled water, 20 parts of distilled water, and 15 parts of butyl titanate are mixed and stirred at 50 ° C for 3 hours, and then 1 part of perfluorodecyl triethoxysilane is added, and after continuing to stir for 2 hours, centrifugal drying is performed to obtain hydrophobic functionalized nano titanium dioxide. 15 parts of hydrophobic titanium dioxide, 5 parts of hydroxy acrylic resin, 25 parts of ethanol and 5 parts are mixed, and a mixed emulsion is obtained by stirring at 500r / min for 30 minutes with a stirrer with a four-blade stainless steel stirring paddle. The mixed emulsion and 100 parts of sol-gel deposited silica sand are placed in a 200ml beaker, and 1 part of polyisocyanate prepolymer curing agent is added after uniformly stirring at 80 ° C and 300r / min for 30 minutes with a stirrer with a four-blade stainless steel stirring paddle, and then drying is performed after continuing to stir for 1 hour to obtain a stable super-hydrophobic artificial colored sand.

[0011] Furthermore, the waterborne epoxy resin dispersion is of bisphenol A type.

[0012] Furthermore, the water-based epoxy curing agent is a polyamine curing agent.

[0013] Furthermore, the silica sand is an inorganic substance mainly composed of silicon, such as natural wind sand and waste glass.

[0014] Furthermore, the solid content of the hydroxy acrylic resin is 30-34%.

[0015] The beneficial effects of the present invention are: The present invention uses carboxylated titanium dioxide as a zinc ion chelating site, titanium dioxide carrying zinc ions on the surface as a zinc source, and synthesizes micro-nanostructured photocatalytic functional particles through a hydrothermal reaction with imidazole. Compared with titanium dioxide, the particles have a higher pore size and specific surface area, that is, a higher photocatalytic activity.

[0016] The present invention uses the composite grafting of disilane as the active site, chemically bonds the waterborne epoxy resin through the site, and then increases the binding force between the filler and the film-forming material while achieving the state where the hydrophilic and hydrophobic groups coexist on the particles, thereby preparing the super-hydrophobic functionalization of the pure water-based system. It has the premise advantage of being greener and more environmentally friendly.

[0017] The present invention uses a hybrid emulsion with photocatalytic and super-hydrophobic composite functions as a new film-forming material, and uses super-hydrophobic watercolor sand as a new functional filler. Compared with traditional super-hydrophobic coatings, the present invention not only gives them the function of photocatalytic oil removal, but also the two exist in the coating in multiple layers in an alternating manner, giving the coating a "self-repairing" function, and having better wear resistance and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The static water contact angle morphology and angle diagram of six groups of samples of the present invention; Figure 2 It is a schematic diagram of the photocatalytic testing device of the present invention; Figure 3 Graph showing the photocatalytic degradation efficiency of six groups of samples of the present invention. DETAILED DESCRIPTION Example 1

[0019] 13 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 3 parts of γ-aminopropyl triethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain titanium dioxide gel solution A with activation sites. 5 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to emulsion B, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained. Example 2

[0020] 13 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 4 parts of γ-aminopropyl triethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain titanium dioxide gel solution A with activation sites. 5 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to emulsion B, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained. Example 3

[0021] 13 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 5 parts of γ-aminopropyl triethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain titanium dioxide gel solution A with activation sites. 5 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to emulsion B, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained.

[0022] Comparative Example 1 10 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 4 parts of γ-aminopropyl triethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain titanium dioxide gel solution A with activation sites. 3 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to emulsion B, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained.

[0023] Comparative Example 2 13 parts of titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 4 parts of γ-aminopropyltriethoxysilane were added and dispersed and stirred at 500r / min for 1h to obtain a titanium dioxide gel solution A with activation sites. 4 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after uniform stirring at 300r / min for 30min to obtain aqueous epoxy / aqueous fluorocarbon hybrid emulsion B. Gel A was added to emulsion B, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained.

[0024] Comparative Example 3 13 parts of composite functional nano-titanium dioxide were dispersed in 6 parts of anhydrous ethanol, and 4 parts of γ-aminopropyltriethoxysilane were added and dispersed and stirred at 500 r / min for 1 hour to obtain a titanium dioxide gel solution A with activation sites. 3 parts of water-based fluorocarbon resin were dispersed in gel A, and 50 parts of super-hydrophobic colored sand were added, and the system was stirred at 300-500 r / min to make the system uniform. After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating was obtained.

[0025] Test 1: The three groups of examples and three groups of comparative examples were tested for wear resistance stability, i.e., a wear test was performed using 800 mesh silicon carbide sandpaper as the wear surface, and then a 100 g load was applied to the sandpaper. After 80 sandpaper wear cycles, the static water contact angle was tested. When WCA ≥ 150°, the surface wetting state reached super hydrophobicity.

[0026] Analysis: The static water contact angle morphology and angle of the six groups of samples are as follows Figure 1 As shown. The WCA of the three groups of embodiments is greater than 150°, and the infiltration state reaches super-hydrophobicity. The WCA of Comparative Example 1 is 137.6°. This is because in Comparative Example 1, we reduced the amount of titanium dioxide particles with composite functions, which resulted in the particles being coated with aqueous emulsion and only a few exposed on the outer surface of the coating, and could not form a regular rough structure, thereby affecting the surface energy of the coating surface, which resulted in a decrease in the hydrophobicity of the coating. Comparative Example 2 also reached a super-hydrophobic state, because the titanium dioxide particles provided a surface roughness comparable to that of titanium dioxide with composite functions. In Comparative Example 3, we did not add water-based epoxy resin, because the titanium dioxide with composite functions failed to form a chemical bond with the film-forming emulsion, and thus could not promote the entire coating system to form a network structure on the surface, reducing the mechanical properties of the coating, and the coating surface showed particle peeling, which ultimately reduced the hydrophobicity of the coating. This shows that a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating can be prepared under the action of multiple aspects such as titanium dioxide with composite functions and water-based epoxy resin. Test 2: The photocatalytic performance of the coating was tested on three groups of examples and three groups of comparative examples. Specifically, in order to ensure that the dye was in full contact with the surface of the photocatalytic coating, a 50 mg / L Rh B solution (100 mL) was filled in a bottomless glass tube (ø40 mm × 35 mm) on the photocatalytic coating sample. All samples were tested under UV-visible light to simulate the actual performance of the samples under natural conditions. The distance between the light source and the coating surface was controlled at a constant value of 50 cm. The removal of Rhodamine B in each group of samples was studied by sampling from the glass tube for up to 150 min at a given 30 min interval.

[0027] Analysis: Photocatalytic test device such as Figure 2 The photocatalytic degradation efficiency of the six groups of samples is shown in Figure 3As shown. The three groups of embodiments have different photocatalytic activities, because different addition amounts of γ-aminopropyltriethoxysilane will affect the light absorption characteristics of TiO2, change its band gap or surface state, and thus affect its photocatalytic efficiency. The photocatalytic effects of Comparative Examples 1 and 2 are poor, because in Comparative Example 1, we reduced the amount of titanium dioxide particles with composite functions, which resulted in the particles being coated by aqueous emulsion and only a few exposed on the outer surface of the coating, and the coating released fewer hydroxyl radicals and superoxide radicals, resulting in poor photocatalytic effects. In Comparative Example 2, we used unfunctionalized titanium dioxide particles. Although pure titanium dioxide has a photocatalytic effect, compared with functionalized titanium dioxide, pure titanium dioxide has fewer active points and a low photocatalytic conversion rate. Comparative Example 3 has a higher photocatalytic effect, because due to the lack of addition of water-based epoxy resin, the functional particles on the coating surface failed to chemically bond with the film-forming emulsion, the coating stability was poor, and the particles were suspended in the dye, resulting in increased photocatalytic activity.

Claims

1. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating, characterized in that: The method specifically comprises the following preparation steps: 13 parts of composite functional titanium dioxide were dispersed in 6 parts of anhydrous ethanol, 4 parts of γ-aminopropyltriethoxysilane were added, and the mixture was dispersed and stirred at 500 r / min for 1 hour to obtain a titanium dioxide gel solution A with activation sites; 5 parts of aqueous epoxy dispersion and 3 parts of aqueous fluorocarbon resin were dispersed in 2 parts of distilled water, and 3 parts of aqueous epoxy curing agent were added after being uniformly stirred at 300 r / min for 30 minutes to obtain an aqueous epoxy / aqueous fluorocarbon hybrid emulsion B; gel A was added to gel B, and 50 parts of super-repellent water-repellent sand were added, and the mixture was stirred at 300-500 r / min to make the system uniform to obtain a water-friendly emulsion; After curing at 70°C, a multi-layer alternating new super-hydrophobic self-cleaning water-based environmentally friendly coating is obtained.

2. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The weight proportions of the raw material components are: 10-15 parts of composite functional titanium dioxide, 50-100 parts of super-repellent color sand, 3-5 parts of γ-aminopropyl triethoxysilane, 5-10 parts of water-based epoxy dispersion, 3-5 parts of water-based fluorocarbon resin, and 3-5 parts of water-based epoxy curing agent.

3. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The steps for preparing composite functional titanium dioxide are as follows: 3 parts of succinic anhydride and 5 parts of γ-aminopropyltriethoxysilane are added to a beaker containing 50 parts of N,N-dimethylformamide, 1 part of 4-dimethylaminopyridine catalyst is added at 80°C, titanium dioxide is added after stirring at 500 r / min for 3 hours, stirring is continued for 2 hours, and centrifugation is performed to obtain carboxylated titanium dioxide; Disperse carboxylated titanium dioxide in 5 parts of anhydrous ethanol, add 10 parts of zinc nitrate after ultrasonic dispersion for 10 minutes, and magnetically stir for 30 minutes for further use; disperse 10 parts of 2-methylimidazole in 3 parts of anhydrous ethanol, add to the above solution, continue stirring for 4 hours, and centrifuge and dry to obtain TiO2 / ZIF-8; disperse 2 parts of TiO2 / ZIF-8 in 10 parts of anhydrous ethanol, add 1 part of perfluorodecyltrimethoxysilane, magnetically stir for 2 hours, and centrifuge and dry to obtain composite functional titanium dioxide.

4. The method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The preparation steps of super-hydrophobic colored sand are as follows: 20 parts of anhydrous ethanol, 10 parts of distilled water, 20 parts of distilled water, and 15 parts of butyl titanate are mixed and stirred at 50°C for 3 hours, then 1 part of perfluorodecyl triethoxysilane is added, stirring is continued for 2 hours, and centrifugal drying is performed to obtain hydrophobic functionalized nano titanium dioxide; 15 parts of hydrophobic titanium dioxide, 5 parts of hydroxy acrylic resin, 25 parts of ethanol and 5 parts are mixed, and a mixed emulsion is obtained by stirring at a speed of 500r / min for 30 minutes with a stirrer with a four-blade stainless steel stirring paddle to obtain a mixed emulsion; the mixed emulsion and 100 parts of sol-gel deposited silica sand are placed in a 200ml beaker, and a stirrer with a four-blade stainless steel stirring paddle is used to uniformly stir at 80°C and a speed of 300r / min for 30 minutes, then 1 part of polyisocyanate prepolymer curing agent is added, stirring is continued for 1 hour, and then drying is performed to obtain stable super-hydrophobic artificial colored sand.

5. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The waterborne epoxy dispersion is of bisphenol A type.

6. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The water-based epoxy curing agent is a polyamine curing agent.

7. A method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The silica sand is an inorganic substance mainly composed of natural wind sand and waste glass silicon.

8. The method for preparing a multi-layer alternating super-hydrophobic self-cleaning water-based environmentally friendly coating according to claim 1, characterized in that: The solid content of the hydroxy acrylic resin is 30-34%.

Citation Information

Patent Citations

  • Asphalt pavement hydrophobic material and preparation process thereof

    CN116445054A

  • Preparation method of super-hydrophobic antibacterial artificial colored sand with stable state

    CN118405873A

  • Coating material having photocatalytic action and additive for coating material

    JP2005139403A

Cited By

  • Industrial anticorrosive paint and preparation method thereof

    CN121450204A

  • An industrial anti-corrosion coating and its preparation method

    CN121450204B